Are business forecasts of the construction sector rational? Survey-based evidence from Malaysia - Puah, Chin Hong; Wong, Shirly Siew-Ling; Muzafar Shah, Habibullah (Taylor & Francis Group, 2017)
This paper extends the direct measure to business expectations in assessing the doctrine of forecast rationality in the contemporary environment of Malaysia’s construction sector. The survey’s expectational series on business operational forecasts across the period 1990 to 2010 is inconsistent with Muth’s concept of rational expectations. Although strict rationality failed to be evidenced, weakly rational conduct can be observed in capital expenditure forecasts. Nevertheless, both operational variables in question are optimistically biased upward and neither of them can accurately reflect the true market perception. This evidence casts doubt on the usefulness of the investigated survey series in providing a realistic panorama of the construction sector in the near future. Notwithstanding, the irrational upshot may drop a hint to the reader on the root of alarming property overhang and price hikes in construction-related markets since expectations play a foremost role in providing equilibrium in the supply and demand in this growth-initiating market.